2014
DOI: 10.1021/am501382y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide-Supported Gold Nanostars for Improved SERS Sensing and Drug Delivery

Abstract: Development of novel surface-enhanced Raman scattering (SERS) substrates and how they interface target analytes plays a pivotal role in determining the spectrum profile and SERS enhancement magnitude, as well as their applications. We present here the seed-mediated growth of reduced graphene oxide-gold nanostar (rGO-NS) nanocomposites and employ them as active SERS materials for anticancer drug (doxorubicin, DOX) loading and release. By this synthetic approach, both the morphology of rGO-NS nanohybrids and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(118 citation statements)
references
References 35 publications
0
118
0
Order By: Relevance
“…When hybridized with gold or silver nanoparticles, graphene-based nanocarriers can serve as active materials for surface enhanced Raman scattering (SERS) experiments for monitoring the process of drug delivery [37,38,56,59,79]. When hybridized with magnetic nanoparticles, graphene-based nanomaterials can be used as magnetic materials for MR imaging [36,39,46,47,80].…”
Section: Graphene-nanoparticle Nanohybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…When hybridized with gold or silver nanoparticles, graphene-based nanocarriers can serve as active materials for surface enhanced Raman scattering (SERS) experiments for monitoring the process of drug delivery [37,38,56,59,79]. When hybridized with magnetic nanoparticles, graphene-based nanomaterials can be used as magnetic materials for MR imaging [36,39,46,47,80].…”
Section: Graphene-nanoparticle Nanohybridsmentioning
confidence: 99%
“…The as-prepared Au-GO nanohybrid can not only be used for intracellular Raman imaging in HeLa cells, but can also be exploited to deliver DOX into cancer cells for chemotherapy, as shown in Figure 3. Wang and co-workers conjugated Au nanostars onto the surface of rGO through a seed-mediated growth method, and the synthesized Au@rGO nanocomposites showed an improved colloidal stability, and sensitive SERS response toward Raman-active molecules [79]. These nanocomposites can be used as an active SERS material for anticancer DOX loading and pH-dependent release.…”
Section: Graphene-nanoparticle Nanohybridsmentioning
confidence: 99%
“…These rGO-NS nanocomposites have the potential to be exploited as a theranostic platform for combined drug delivery and Raman imaging. 144 …”
Section: Raman Imaging-guided Drug Deliverymentioning
confidence: 99%
“…For instance, in several studies on the delivery of the anticancer drug doxorubicin, it has been revealed that graphene oxide (GRO) played an effective role in the delivery and release of the drug into the targeted cancer cell. 15,16 Apart from this, several other studies have also been published regarding the applications of graphene and graphene-based materials for various biological purposes due to their extraordinary physicochemical properties, such as mechanical properties, electrical properties, electrochemical properties, and thermal conductivity. 14,[17][18][19][20][21][22][23][24] However, despite the recent surge in such studies, a lot more needs to be done in order to fully exploit the potential of graphene-based materials in biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…28 Additionally, trace amounts of toxic-reducing agents present on the surface of these materials could seriously affect the potential properties of highly reduced graphene oxide (HRG) and have undesirable effects on its biological applications. 16 Whereas, the green synthesis of graphene-based materials involves biocompatible ingredients under physiological conditions of temperature and pressure. 29,30 Among various methods, plant extract (PE)-based syntheses of graphene and graphene-based materials have attracted significant attention due to their bulk availability, biocompatibility, and low cost.…”
Section: Introductionmentioning
confidence: 99%